Developing Legal-Entity Higher Education Institution (Perguruan Tinggi Negeri – Badan Hukum) as Centre of Excellence - Fachriansyah, Kalihputro; Sulastri, Endang (Bappenas Working Papers, 2020)
In the era of the knowledge and digital economy today, technology is no longer meant as a tool to increase productivity. Instead, it becomes a critical factor in creating added value. Higher education as an institution that is responsible for advancing science while producing innovative products of high economic value needs to be encouraged as a Centre of Excellence (CoE). Among others, Legal-Entity Higher Education Institution/Perguruan Tinggi Badan Hukum (PTN-BH) is considered more potential to become CoE in Indonesia because it has the autonomy of academic and non-academic management. Utilizing CoE criteria such as financial/funding, cooperation, governance, academic, and research-innovation, a gap analysis was conducted to find out what are best policies to develop PTN-BH towards CoE. This study suggests that the centre of science and technology excellence/Pusat Unggulan Iptek (PUI) can be a promising starting point towards CoE.